The Relationship of the Inter-pregnancy Interval with Adverse Birth Outcomes - Salwa Hazim Al-Mukhtar (Kufa Journal for Nursing Sciences)
Background: The inter-pregnancy interval is the time between the last delivery and conception of the current pregnancy. Also, known as birth spacing,